2021
DOI: 10.1002/adma.202003786
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Nonprecious‐Metal‐Based Electrocatalysts for Oxygen Evolution in Acidic Media

Abstract: Water oxidation, or the oxygen evolution reaction (OER), which combines two oxygen atoms from two water molecules and releases one oxygen molecule, plays the key role by providing protons and electrons needed for the hydrogen generation, electrochemical carbon dioxide reduction, and nitrogen fixation. The multielectron transfer OER process involves multiple reaction intermediates, and a high overpotential is needed to overcome the sluggish kinetics. Among the different water splitting devices, proton exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
135
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(154 citation statements)
references
References 181 publications
1
135
0
Order By: Relevance
“…Recently, operando spectroscopies have identified that transition metal‐based oxyhydroxides are further be deprotonated to generate high‐valent species, which are regarded as the active species for OER. For example, according to the potential‐pH Pourbaix diagram of Co‐based materials, Co 4+ species will be formed first before the potential of OER under alkaline conditions, suggesting the Co 4+ species is the key intermediate [18–20] . Sargent et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, operando spectroscopies have identified that transition metal‐based oxyhydroxides are further be deprotonated to generate high‐valent species, which are regarded as the active species for OER. For example, according to the potential‐pH Pourbaix diagram of Co‐based materials, Co 4+ species will be formed first before the potential of OER under alkaline conditions, suggesting the Co 4+ species is the key intermediate [18–20] . Sargent et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high price of raw materials compels researchers to find new approaches. Transition metal (ie, Cu, Fe, Ni, and Co) composites are the best candidates to replace the expensive electrocatalysts based on the noble metals 9‐11 . Specifically, oxides, sulfides, carbides, and phosphides of transition metals exhibit superior performance and stability in electrocatalytic (EC) HER, OER, and direct MOR, in some cases outperforming the benchmark Pt/C in HER, Ir/C in OER, and Pd‐based catalysts in MOR 11‐16 .…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal (ie, Cu, Fe, Ni, and Co) composites are the best candidates to replace the expensive electrocatalysts based on the noble metals. [9][10][11] Specifically, Talshyn Begildayeva, Deviprasath Chinnadurai, and Seung Jun Lee contributed equally to this work. oxides, sulfides, carbides, and phosphides of transition metals exhibit superior performance and stability in electrocatalytic (EC) HER, OER, and direct MOR, in some cases outperforming the benchmark Pt/C in HER, Ir/C in OER, and Pd-based catalysts in MOR.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations